Providing Advice to Job Seekers at Low Cost: An Experimental Study on On-Line Advice. - Michèle Belot; Philipp Kircher; Paul Muller (Center for Economic Studies and ifo Institute (CESifo), 2015)
Helping job seekers to identify suitable jobs is a key challenge for policy makers. We develop and evaluate experimentally a novel tool that provides tailored advice at low cost and thereby redesigns the process through which job seekers search for jobs. We invited 300 job seekers to our computer facilities for 12 consecutive weekly sessions. They searched for real jobs using our web interface. After 3 weeks, we introduced a manipulation of the interface for half of the sample: instead of relying on their own search criteria, we displayed relevant other occupations to them and the jobs that were available in these occupations. These suggestions were based on background information and readily available labor market data. We recorded search behavior on our site but also surveyed participants every week on their other search activities, applications and job interviews. We find that these suggestions broaden the set of jobs considered by the average participant. More importantly, we find that they are invited to significantly more job interviews. These effects are predominantly driven by job seekers who searched relatively narrowly initially and who have been unemployed for a few months.
Keywords: D83; J62; C93; 330; online job search; occupational broadness; search design